Effect of Particle Size on Microstructure and Mechanical Properties of Al-Based Composite Reinforced with 10 Vol.% Mechanically Alloyed Mg-7.4%Al Particles - Chaubey A.K.; Konda Gokuldoss P.; Wang Z.; Scudino S.; Mukhopadhyay N.K.; Eckert J. (My University, 2025)
The effect of Mg-7.4%Al reinforcement particle size on the microstructure and mechanical properties in pure Al matrix composites was investigated. The samples were prepared by hot consolidation using 10 vol.% reinforcement in different size ranges, D, 0 < D < 20 µm (0–20 µm), 20 ≤ D < 40 µm (20–40 µm), 40 ≤ D < 80 µm (40–80 µm) and 80 ≤ D < 100 µm (80–100 µm). The result reveals that particle size has a strong influence on the yield strength, ultimate tensile strength and percentage elongation. As the particle size decreases from 80 ≤ D < 100 µm to 0 < D < 20 µm, both tensile strength and ductility increases from 195 MPa to 295 MPa and 3% to 4% respectively, due to the reduced ligament size and particle fracturing. Wear test results also corroborate the size effect, where accelerated wear is observed in the composite samples reinforced with coarse particles. © 2016 by the authors; licensee MDPI, Basel, Switzerland.